2012
DOI: 10.3727/096504012x13548165987493
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ZFX in Non-Small Cell Lung Cancer Development

Abstract: Zinc finger protein, X-linked (ZFX) is a transcription factor encoded by its gene on the mammalian X chromosome, and functions to control survival and activity of stem cells and lymphocytes. However, little is known about the role of ZFX in tumorigenesis. The function of ZFX in cell proliferation was investigated by the lentivirus-mediated short hairpin RNA interference (shRNA) approach in non-small cell lung cancer (NSCLC) cell culture lines. The expression profiles of ZFX in 49 pairs of tumors and correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…ZFX is the X-linked version of a protein that plays a role in molecular sex determination [ 61 ], so it may not be surprising that we found sex-specific differences in its regulatory patterns. However, it has also been implicated in lung cancer [ 62 , 63 ]. Similarly CREB is over-expressed in many cancers, including lung cancer [ 64 ], and, interestingly, has been shown to interact with the estrogen receptor and to have age and sex- dependent expression patterns in the human brain [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…ZFX is the X-linked version of a protein that plays a role in molecular sex determination [ 61 ], so it may not be surprising that we found sex-specific differences in its regulatory patterns. However, it has also been implicated in lung cancer [ 62 , 63 ]. Similarly CREB is over-expressed in many cancers, including lung cancer [ 64 ], and, interestingly, has been shown to interact with the estrogen receptor and to have age and sex- dependent expression patterns in the human brain [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, ZFX was recently revealed to be a transcriptional target of cyclin D1 [27], linking ZFX to an established oncogene product and oncogenic pathway in parathyroid and other cell types. Further, knockdown of ZFX has been reported to inhibit cellular proliferation in human laryngeal squamous cell carcinoma, gastric cancer, malignant glioma, non-small cell lung carcinoma and prostate cancer [28][29][30][31][32]. Finally, a solitary ZFX R786Q somatic mutation in endometrial carcinoma has been registered in the COSMIC database (endometrial cancer; mutation ID: COSM1119462).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these proteins, ZFX is a member of the zinc finger protein family. Previous studies have demonstrated that ZFX can function as an oncoprotein in various types of cancers, including gastric cancer [ 16 ], prostate cancer [ 24 , 25 ], glioma [ 26 ], hepatocellular cancer [ 30 ], gallbladder cancer [ 31 ], tongue squamous cell carcinoma [ 32 ], non-small cell lung cancer [ 33 ], and laryngeal squamous cell carcinoma [ 34 ]. However, few studies have focused on the prognostic significance of ZFX in RCC.…”
Section: Discussionmentioning
confidence: 99%